Case report of a male child with lupus nephritis - ., Richa; Sharma, Shashi; Abrol, Pankaj (International Journal of Contemporary Pediatrics, 2019)
Systemic lupus erythematosus is a chronic autoimmune inflammatory disease of unknown etiology that affects various organs, most frequently the skin, joints, kidneys, nervous, hematologic and cardiovascular systems. It affects females more often as compared to males. The kidneys are one of the most serious organs involved. Lupus nephritis may present as hypertension, proteinuria, and renal failure or it may also be asymptomatic. The recent reports suggest that childhood-onset lupus nephritis could be more severe than the late-onset disease. The occurrence of SLE in pediatric patients is very rare, especially in a male child. Here author report a case of an 8-year-old male child clinically misdiagnosed as a case of henoch schonlein purpura, who was thoroughly investigated and finally confirmed as a case of lupus nephritis.